Potassium Salts of 2, 5‐Bis(trimethylsilyl)‐Germolide: Switching between Aromatic and Non‐Aromatic States. Issue 46 (24th July 2019) - Dong, Zhaowen; Schmidtmann, Marc; Müller, Thomas
Abstract: Invited for the cover of this issue is the group of Thomas Müller at the University of Oldenburg. The image depicts the switch between aromatic and non‐aromatic states of a potassium germacyclopentadienide triggered by complexation of the potassium cation. Read the full text of the article at10.1002/chem.201902238 . Abstract : " The unexpected facile switch between aromatic and non‐aromatic states of a germole anion that is initiated by complexation of the potassium counter cation is the central result of the here highlighted research ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 10858 ff. (DOI:10.1002/chem.201902238 ).